Vacancy analysis and layout optimization of Changdao natural protected area from the perspective of multi-objective collaboration - He, Shuai; Xia, Tao; Luo, Meixue; Li, Wenwen; Zhang, Junxin; Li, Yanxiang; Chen, Shang (Frontiers in Ecology and Evolution, 2023)
Research on vacancy analysis and spatial layout of protected natural areas has been carried out for many years around the world, but most of the research objects are land-type protected natural areas, while studies on Marine protected natural areas are relatively rare, and there are few cases to carry out integrated optimization research on spatial layout of protected natural areas. This study will take Changdao in Yantai, Shandong Province, China as an example, from the protection of how much? How representative? Where is it protected? Starting from the three problems, the vacancy analysis is carried out, and the integrated optimization research is carried out based on the existing spatial layout, aiming at the rescue protection, coordinated protection and forward-looking protection. The results show that the integrated and optimized Changdao protected area eliminates the protection vacancy, integrates the overlapping protected areas, optimizes the unreasonable protected space, alleviates the contradiction between protection and development, promotes the coordinated development of ecology and economy and society, and can provide a scientific reference for the integrated and optimized spatial layout of Marine protected areas.